Favorable 2 '-substitution in the loop region of a thrombin-binding DNA aptamer - Awachat, Ragini; Wagh, Atish A.; Aher, Manisha; Fernandes, Moneesha; Kumar, Vaijayanti A. (Bioorganic & Medicinal Chemistry Letters, 2018)
Simple 2'-OMe-chemical modification in the loop region of the 15mer G-rich DNA sequence GGTTGGTGTGGTTGG is reported. The G-quadruplex structure of this thrombin-binding aptamer (TBA), is stabilized by single modifications (T -> 2'-OMe-U), depending on the position of the modification. The structural stability also renders significantly increased inhibition of thrombin-induced fibrin polymerization, a process closely associated with blood-clotting. (C) 2018 Elsevier Ltd. All rights reserved.